2009
DOI: 10.1038/jid.2008.370
|View full text |Cite
|
Sign up to set email alerts
|

Highly Complex Peptide Aggregates of the S100 Fused-Type Protein Hornerin Are Present in Human Skin

Abstract: Human hornerin (HRNR) is a 245 kDa S100 fused-type protein which contains 95% tandem quasi-repeating glycine- and serine-rich domains. Previously HRNR was not thought to be expressed in healthy skin; however, we purified an HRNR peptide fragment from stratum corneum. Moreover, we found that HRNR mRNA is expressed in skin biopsies from different sites as head, trunk, legs, hands, and feet. In cultured human epidermal keratinocytes, HRNR mRNA expression was transiently induced during Ca(2+)-dependent differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 56 publications
2
79
0
3
Order By: Relevance
“…SFTP genes consist of three exons, a tiny untranslated exon 1, a small exon 2 containing the translation start site and encoding a 46-residue S100 domain, and a large exon 3 encoding an EF-hand domain and internal tandem repeats, which are characteristic of cornified envelope precursor proteins. Recently a repeat domain of hornerin was identified in human stratum corneum (Wu et al 2009b), pointing to a proteolytic processing of this 245-kDa protein, which contains 95% tandem quasirepeating glycine-and serine-rich domains. It was reported that the proteolytic products of hornerin form high-molecular aggregates which might have special characteristics such as water-binding and elastic properties.…”
Section: Filaggrinmentioning
confidence: 99%
“…SFTP genes consist of three exons, a tiny untranslated exon 1, a small exon 2 containing the translation start site and encoding a 46-residue S100 domain, and a large exon 3 encoding an EF-hand domain and internal tandem repeats, which are characteristic of cornified envelope precursor proteins. Recently a repeat domain of hornerin was identified in human stratum corneum (Wu et al 2009b), pointing to a proteolytic processing of this 245-kDa protein, which contains 95% tandem quasirepeating glycine-and serine-rich domains. It was reported that the proteolytic products of hornerin form high-molecular aggregates which might have special characteristics such as water-binding and elastic properties.…”
Section: Filaggrinmentioning
confidence: 99%
“…This sequence is specific for human pro-filaggrin and shows no homology to mouse or human hornerin (25,26) or filaggrin-2 (27). Antibodies were purified using antigen-coupled affinity chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The following antibodies were used: antibodies against filaggrin (1:6000; Biomedical Technologies Inc.); loricrin (1:500; BabCO); involucrin (1:50; Mon150; generated by our lab, van Duijnhoven [1992], University of Geneva, Switzerland); and hornerin (antibody was raised against full-length recombinant HRNR repeat domains, 1:200; ref. 59). For translocation of AHR and NRF2 (1:200, Santa Cruz), direct immunofluorescence labeling was performed using Alexa Fluor 488 conjugate in conjunction with fluorescence microscopy, and fluorescence intensity of nuclei and cytoplasm was measured by ImageJ software.…”
Section: Figurementioning
confidence: 99%